PEMBELAJARAN MATERI PAI BERWAWASAN MULTIKULTURAL - Khoiruman Khoiruman (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2020)
PAI Subject matter  learning based multicultural is PAI subject matter learning that try to develop student competency in receiving human being differences, in order that student can live together in differences, they can build the mutual trust between multicultural community, the mutual respect, interdependence, open relationship in thought, increase relations unity and harmony with their friends or people of different background religious, ethnic, cultural, economic, as well as normal. PAI Subject matter  learning based multicultural will get evective result if it notices three components, namelly: (1) the conditions of PAI Subject matter  learning based multicultural; (2) the methods of PAI Subject matter  learning Based Multicultural; (3) the outcomes of PAI learning subject matter  Based multicultural. This study aims to usher students reaching for four pillars of learning experience, namelly:(1) learning to know; (2) learning to do; (3) learning to be; (4) and learning to live together.